The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/tea.21632
|View full text |Cite
|
Sign up to set email alerts
|

Professional knowledge affectsaction‐relatedskills: The development ofpreservicephysics teachers' explaining skills during a field experience

Abstract: Professional knowledge is an important source of science teachers' actions in the classroom (e.g., personal professional content knowledge [pedagogical content knowledge, PCK] is the source of enacted PCK in the refined consensus model [RCM] for PCK). However, the evidence for this claim is ambiguous at best. This study applied a cross‐lagged panel design to examine the relationship between professional knowledge and actions in one particular instructional situation: explaining physics. Pre‐ and post a field e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
0
31
0
3
Order By: Relevance
“…There is also evidence that, after receiving feedback from their mentor during teaching placements, prospective teachers' explanations improved in later lessons (Borko et al 1992;Eisenhart et al 1993). In respect of field placements, Kulgemeyer et al (2020) showed that professional knowledge prior to the teaching placement (pre-test) influenced explaining skills after the teaching placement (post-test). In fact, only teacher candidates entering the school internship with high professional knowledge showed significant development in explaining skills after a 5-month placement.…”
Section: Empirical Evidence On Teacher Candidates' Explaining Skillsmentioning
confidence: 99%
“…There is also evidence that, after receiving feedback from their mentor during teaching placements, prospective teachers' explanations improved in later lessons (Borko et al 1992;Eisenhart et al 1993). In respect of field placements, Kulgemeyer et al (2020) showed that professional knowledge prior to the teaching placement (pre-test) influenced explaining skills after the teaching placement (post-test). In fact, only teacher candidates entering the school internship with high professional knowledge showed significant development in explaining skills after a 5-month placement.…”
Section: Empirical Evidence On Teacher Candidates' Explaining Skillsmentioning
confidence: 99%
“…PSTs encounter learning opportunities during university teacher education addressing different components of PCK. Explicit instruction in science method courses supports preservice teachers' knowledge exchange between cPCK and pPCK (Sorge, Stender et al, 2019), and field experiences provide opportunities for preservice teachers to enrich their pPCK (van Driel et al, 2002) and develop their ePCK for planning, teaching and reflecting Kulgemeyer et al, 2020).…”
Section: Pedagogical Content Knowledgementioning
confidence: 99%
“…Recently, the connections between pre-service teachers' explanations and PCK have been empirically supported. We know now that science pre-service teachers' PCK is a mediator of their explaining performance; then, PCK affects their enacted knowledge to explain (Kulgemeyer & Riese, 2018;Kulgemeyer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The construct of such an explanatory framework enriched the idea of explanation as an answer to a why-question, highlighting how teachers use analogy, metaphor, examples, axioms and concepts, linking them together into a coherent whole for the classroom (Geelan, 2003). However, constructing explanations is a complicated process, and many teachers struggle to transform academic knowledge into explanations for the school (Cabello, Real, & Impedovo, 2019;Charalambous, Hill, & Ball, 2011;Gobierno de Chile, 2013;Hadzidaki, 2008;Kulgemeyer, et al, 2020;Inoue, 2009;Wittwer & Renkl, 2008). Indeed, this is even more critical for beginner teachers (Leinhardt, 2001;Ospina-Quintero & Bonan, 2011;Marzabal et al, 2019), and practical experience without reflection is unlikely to automatically lead to better results in explaining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation